Update: NOVA - team, Update (World Nutrition, 2013)
Special coverage of the IUNS conference in Granada, Spain:IUNS Granada: The Bellagio Declaration on Big FoodIUNS Granada: The Bellagio INFORMAS Declaration on obesityIUNS Granada: The Food System NOVA food classificationGut bugs – the bad that are good.